Effects of Hot Water Treatments on Antioxidant Enzymatic System in Reducing Flesh Browning of Persimmon - Khademi, Orang; Salvador, Alejandra; Zamani, Zabiollah; Besada, Cristina (2017)
The flesh browning that appears during commercialization period is the main postharvest disorder that is limiting the market of "Rojo Brillante" persimmon in the Mediterranean area. Previous studies have suggested that mechanical damage suffered by the fruit during packing line operations is the trigger of this alteration when fruit is previously subjected to the required deastringecy treatment. In the present work, the effect of hot water treatments (HWTs) on flesh browning incidence of Rojo Brillante persimmon has been investigated. For that, fruits submitted to the commercial deastringency treatment were hot water treated at 45 A degrees C for 30 min or 50 A degrees C for 20 min and then subjected to different intensity of mechanical damage in packing line. Fruit bathed at 25 A degrees C for 25 min and fruit hand-packed acted as control treatments. Our results confirmed that mechanical damage during packing is a decisive factor in the incidence of flesh browning, and this alteration is found to increase the damage intensity. HWTs significantly alleviated flesh browning disorder by affecting the antioxidative system enzymes; the activity of catalase and ascorbate peroxidase was increased by HWTs while the activity of peroxidases was reduced. No changes were observed in polyphenol oxidase and phenylalanine ammonia lyase activity. Therefore, the application of HWTs may be a useful postharvest technology to reduce flesh browning of persimmon induced by packing line operations.